Answer:
x=-2
Step-by-step explanation:
Answer:
Step-by-step explanation:
<u>Given system of linear equations: </u>
---
- x + 4 = -3x - 8
- x + 3x = - 8 - 4
- 4x = -12
- x = -3
Then
Solution is (-3, 1)
Correct option is A
Problem 11
<h3>Answer: h =
2A/b</h3>
------------------
Explanation:
We need to get h by itself. To do so, we first multiply both sides by 2. Then we divide both sides by b
A = (1/2)*b*h
2A = b*h
b*h = 2A
h = 2A/b
================================================
Problem 12
<h3>Answers:</h3>
- Equation: (n+2)/5 = 14
- Solution to that equation: n = 68
------------------
Explanation:
The number n is increased by 2 to get n+2
Then we divide by 5 to get (n+2)/5
This is set equal to 14 to get the equation (n+2)/5 = 14
Solving the equation would look like this
(n+2)/5 = 14
n+2 = 5*14 .... multiply both sides by 5
n+2 = 70
n = 70-2 .... subtract 2 from both sides
n = 68
================================================
Problem 13
<h3>Answer: Not a solution</h3>
------------------
Explanation:
We'll replace every copy of x with -3 and simplify
-2x + 5 > 13
-2*(-3) + 5 > 13
6 + 5 > 13
11 > 13
The last inequality is false because 11 is not greater than 13. Since the last inequality is false, this makes the first inequality false when x = -3.
Therefore, x = -3 is not a solution.
Answer:
20 = viente
Step-by-step explanation: plz mark brainliest
Answer:find the solution to the system of equations below.start by adding the equation
{-2x+2y=-8
{2x+y=5
Step-by-step explanation:The given system of equation are:
1---- y= x -4
2----- y=4 x+2
Equation (1) - Equation (2)
→0= x -4 - (4 x+2)
→0= -3 x -6-----[Adding and subtracting like terms]
Adding 3 x on both sides
→3 x= -6
Dividing by 3 on both sides
→x = -2
→Substituting the value of x in equation 1, we get
y= -2 -4
y =-6
→Solution set =(x,y)=(-2, -6)
Don't used the graph to find the solution.